A Novel Non-operative Protocol for the Acute Management of In-season Acromioclavicular Separations. Issue 7 (21st July 2017) - Heard, Wendell M.R.; O'Brien, Michael John; Taylor, Daniel; Massey, Andrew; STEWART, GREGORY W.; Savoie, Felix H.
Objectives: Traditional treatment of acromioclavicular (AC) sprains has been a sling with rest and rehabilitation. We have developed a protocol that uses a static scapular retraction brace (Figure 1) to reduce the displaced upper extremity back to the clavicle. We hypothesized that the brace in combination with oral and injected steroid and a rehabilitation protocol that emphasizes postural restoration, facilitates a more anatomic reduction of the AC joint that quickly eliminates discomfort, allows for more anatomic healing and a rapid return to normal activities in type 1, 2, and 3 AC separations. Methods: Data was prospectively collected and retrospectively reviewed on all collegiate football AC separations at an NCAA division I university. Data included treatment, the number of practices missed, the number of games missed, and time to full return to play. Inclusion criteria were all consecutive in-season Type I-III AC separations sustained during football activities that requiring medical attention. Exclusion criteria include fractures, glenohumeral dislocations, rotator cuff tears, nerve injuries, other concomitant shoulder injuries, and injuries sustained during the last game of the season. The end points measured were number of games missed and time to full return to play. Results: During seven football seasons (2008-2014), 56 acromioclavicular separations occurred. Fifty-two (52) AC separations are included in the current study. Full return to play ranged from 0-31 days, with an average 5.7 days to full return to play. On average, athletes missed 0.25 games (range 0-3 games). Quarterbacks missed the most time, and an injury to the quarterback's throwing shoulder required the most time to return to full play (mean 26 days and 3 games). The return to play in our group of athletes was more rapid and than that reported in the literature. Conclusion: The unique aspect of this protocol is anatomic reduction of the AC joint with the use of a static, three-point brace to pull and rotate the entire forequarter back to the clavicle. It is common in fracture reduction to reduce the distal piece to the proximal segment to achieve anatomic restoration. This principle attempts to do the same. A secondary effect of the static reduction is the diminution of rotator cuff pain due to opening the subacromial space by scapular retraction, thus decreasing pressure on the contused supraspinatus tendon and allowing more rapid resolution of the inflammation. This study represents a specific non-operative protocol for the in-season management of AC injuries to quickly and safely return athletes to play.